2017
DOI: 10.1097/ijg.0000000000000720
|View full text |Cite
|
Sign up to set email alerts
|

Practice Preferences for Glaucoma Surgery: A Survey of the American Glaucoma Society

Abstract: Purpose To assess surgical practice patterns among the American Glaucoma Society (AGS) membership. Methods An anonymous online survey evaluating the use of glaucoma surgeries in various clinical settings was redistributed to AGS members. Survey responses were compared with prior results from 1996, 2002, and 2008 to determine shifts in surgical practice patterns. Questions were added to assess the preferred approach to primary incisional glaucoma surgery and phacoemulsification combined with glaucoma surgery.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 196 publications
(111 citation statements)
references
References 33 publications
1
108
0
2
Order By: Relevance
“…Limitations of this study include a low response rate (25%). However, it is comparable to that of the historical control survey on glaucoma practice patterns by Vinod et al (23% response rate) 7,8 and responses were received from all geographic regions of the country. Another limitation is that the survey design did not allow for the distinction between 0 and 1-5 cases for the questions about number of cases residents observed, assisted, and completed as primary surgeons.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Limitations of this study include a low response rate (25%). However, it is comparable to that of the historical control survey on glaucoma practice patterns by Vinod et al (23% response rate) 7,8 and responses were received from all geographic regions of the country. Another limitation is that the survey design did not allow for the distinction between 0 and 1-5 cases for the questions about number of cases residents observed, assisted, and completed as primary surgeons.…”
Section: Discussionsupporting
confidence: 67%
“…Several studies have demonstrated a decline in trabeculectomy cases and increase in glaucoma drainage device implantation over the past 10 years. [5][6][7][8][9][10] Simultaneously, there has been an increase in development and use of MIGS devices. 2,11 MIGS is becoming an important part of the surgical armamentarium for glaucoma surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Meanwhile, DS was not even mentioned in the survey which indicates that it is not one of the favorite glaucoma surgeries for glaucoma surgeons. 20 The steep learning curve is the main reason for not being a popular surgery.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term data regarding cost-effectiveness is currently inexistent. Trabeculectomy is still the cheapest surgical option amongst all glaucoma procedures and the most commonly performed procedure [ 81 , 82 ].…”
Section: Introductionmentioning
confidence: 99%
“…A survey of American Glaucoma society (AGS) published in 2017 for preferred practice preferences for the type of glaucoma surgery among AGS members has also reported that Trab MMC, GDD and MIGS constituted 59±30%, 23±23% and 14±20% respectively as an initial surgery in POAG. Although the use of GDD surgery has increased and trabeculectomy has decreased from 1996 to 2016 [ 81 ], Trab MMC was still the most popular primary glaucoma surgery among surgeons.…”
Section: Introductionmentioning
confidence: 99%